Pembinaan Pemberdayaan Kelompok UKM Berbasis Teknologi Dan Pemasaran Digital - Erlin Elisa; Tukino Tukino; Alfannisa Annurrallah Fajrin; Nanda Harry Mardika; Suvianto Wangdra (Prosiding, 2023)
The implementation of community service activities that will be carried out in the form of fostering Pemasaran Digital-Based Marketing Empowerment which is located at Rindang Garden Blok B2 No. 04 Buliang Batu Aji Village, Batam. Based on the results of interviews in the field that KUBE Jasmine SMEs have problems marketing their products. In general, SMEs have limitations in mastering the use of information technology facilities plus marketing media that are less well known by the public. SMEs or conventional entrepreneurs consider accounting records to be a hassle. The training method used is to provide training on training using an online website. The methods used in the development of KUBE Jasmine UKM that will be given are survey methods, lecture methods, discussion methods and training methods. The sustainability of the results of the coaching activities is that KUBE Jasmine SMEs are expected to be able to manage marketing through web-based Pemasaran Digital.